The Relationship between Safety Knowledge and Safety Motivation with Safety Performance among Constructions Workers of PT.X in Bandung Regency - Dwi Estu Pratiwi; Ro'is, Rachmy Rosidah; Ardyanto Wahyudiono, Yustinus Denny (Universitas Nahdlatul Ulama Surabaya, 2024)
The prevalence of accidents in Indonesia from 2017 to 2021 has increased from 123,040 cases to 234,270 cases yearly.Individuals need to implement safety performance measures. One of the personal factors that affect safety performance is safety knowledge and safety motivation. This study aims to determine the relationship between safety knowledge and motivation with safety performance among construction workers of PT.X in Bandung Regency. This research was conducted during the PT X construction project at Bandung Regency. The research started in November 2022 and finished in January 2023. This study used a quantitative approach with observational analytics and a cross-sectional research design. The study population consists of 127 construction workers employed by PT X in Bandung Regency. The method used in this research is simple random sampling with a minimum sample size required for this study of 96 respondents. Analytics data used the chi-square test to analyze bivariate data with a significance value of 0,05. The independent variables in this study are safety knowledge and safety motivation, while the dependent variables are safety performance. The result of this research showed that there was a relationship between safety knowledge (0.00<0.05) and safety motivation (0.01<0.05) with safety performance. Increasing workers' knowledge of potential hazards, risks, and controls in the construction sector will motivate workers to behave safely in the work environment. Keywords: Safety Knowledge, Safety Motivation, Safety Performance